Long-Term Intermittent Work at High Altitude: Right Heart Functional and Morphological Status and Associated Cardiometabolic Factors - Brito, Julio; Siques, Patricia; López, Rosario; Romero, Raul; León-Velarde, Fabiola; Flores, Karen; Lüneburg, Nicole; Hannemann, Juliane; Böger, Rainer H. (Frontiers in Physiology, 2018)
Background: Living at high altitude or with chronic hypoxia implies functional and morphological changes in the right ventricle and pulmonary vasculature with a 10% prevalence of high-altitude pulmonary hypertension (HAPH). The implications of working intermittently (day shifts) at high altitude (hypobaric hypoxia) over the long term are still not well defined. The aim of this study was to evaluate the right cardiac circuit status along with potentially contributory metabolic variables and distinctive responses after long exposure to the latter condition. Methods: A cross-sectional study of 120 healthy miners working at an altitude of 4400-4800 m for over 5 years in 7-day commuting shifts was designed. Echocardiography was performed on day 2 at sea level. Additionally, biomedical and biochemical variables, Lake Louise scores (LLSs), sleep disturbances and physiological variables were measured at altitude and at sea level. Results: The population was 41.8±0.7 years old, with an average of 14±0.5 (range 5-29) years spent at altitude. Most subjects still suffered from mild to moderate symptoms of acute mountain sickness (mild was an LLS of 3-5 points, including cephalea; moderate was LLS of 6-10 points) (38.3%) at the end of day 1 of the shift. Echocardiography showed a 23% mean pulmonary artery pressure (mPAP) >25 mmHg, 9% HAPH (≥30 mmHg), 85% mild increase in right ventricle wall thickness (≥5 mm), 64% mild right ventricle dilation, low pulmonary vascular resistance and fairly good ventricle performance. Asymmetric dimethylarginine (ADMA) (OR 8.84 (1.18-66.39; p<0.05) and insulin (OR: 1.11 (1.02-1.20; p<0.05) were associated with elevated mPAP and were defined as a cut-off. Interestingly, the correspondence analysis identified association patterns of several other variables (metabolic, labor and biomedical) with higher mPAP. Conclusion: Working intermittently at high altitude involves a distinctive pattern. The most relevant and novel characteristics are a greater prevalence of elevated mPAP and HAPH than previously reported at chronic intermittent hypobaric hypoxia (CIHH), which is accompanied by subsequent morphological chracteristics. These findings are associated with cardiometabolic factors (insulin and ADMA). However, the functional repercussions seem to be minor or negligible. This research contributes to our understanding and surveillance of this unique model of chronic intermittent high-altitude.